Association of Metformin Use With Cancer-Specific Mortality in Hepatocellular Carcinoma After Curative Resection: A Nationwide Population-Based Study. Issue 17 (April 2016) - Seo, Young-Seok; Kim, Yun-Jung; Kim, Mi-Sook; Suh, Kyung-Suk; Kim, Sang Bum; Han, Chul Ju; Kim, Youn Joo; Jang, Won Il; Kang, Shin Hee; Tchoe, Ha Jin; Park, Chan Mi; Jo, Ae Jung; et al.
Abstract : Abstract: Many preclinical reports and retrospective population studies have shown an anticancer effect of metformin in patients with several types of cancer and comorbid type 2 diabetes mellitus (T2DM). In this work, the anticancer effect of metformin was assessed in hepatocellular carcinoma (HCC) patients with T2DM who underwent curative resection. A population-based retrospective cohort design was used. Data were obtained from the National Health Insurance Service and Korea Center Cancer Registry in the Republic of Korea, identifying 5494 patients with newly diagnosed HCC who underwent curative resection between 2005 and 2011. Crude and adjusted hazard ratios (HRs) were calculated using Cox proportional hazard models to estimate effects. In the sensitivity analysis, we excluded patients who started metformin or other oral hypoglycemic agents (OHAs) after HCC diagnosis to control for immortal time bias. From the patient cohort, 751 diabetic patients who were prescribed an OHA were analyzed for HCC-specific mortality and retreatment upon recurrence, comparing 533 patients treated with metformin to 218 patients treated without metformin. In the fully adjusted analyses, metformin users showed a significantly lower risk of HCC-specific mortality (HR 0.38, 95% confidence interval [CI] 0.30–0.49) and retreatment events (HR 0.41, 95% CI 0.33–0.52) compared with metformin nonusers. Risks for HCC-specific mortality were consistently lower among metformin-using groups, excluding patients who started metformin or OHAs after diagnosis. In this large population-based cohort of patients with comorbid HCC and T2DM, treated with curative hepatic resection, metformin use was associated with improvement of HCC-specific mortality and reduced occurrence of retreatment events.